The Use of Politeness Strategies in Academic Conversations as Represented in a Corpus Linguistics MOOC - Mohamed Arafa Hilal (UIN Salatiga, 2023)
Although politeness strategies are widely used in various types of conversations, e.g., formal emails, business, hotel conversations, movies, and others, few works have dealt with politeness strategies in academic conversations. This study attempts to shed light on the use of politeness strategies in academic conversations and to relate these strategies to the relationship between the interlocutors: whether they have the same specialization or not. The study mainly draws on Brown and Levinson's positive politeness strategies and applies them to conversations. The data was collected by downloading conversations from a MOOC entitled